Analisis Kemampuan Berpikir Kritis Siswa SMP melalui Media Digital Wizer.me dengan Konteks Masjid Agung Palembang - Dela Puspita Sari; Elsa Susanti; Weni Dwi Pratiwi; Nurdin Kamil; Yusuf Hartono (FKIP Universitas PGRI Palembang, 2025)
Critical thinking skills are one of the important skills that must be improved in the learning process, especially in the subject of plane geometry. This study aims to analyze how junior high school students' critical thinking skills are developed through the digital media platform Wizer.me in the context of the Grand Mosque of Palembang. Four indicators are used: interpretation, analysis, evaluation, and inference. The method used in this study was descriptive with a qualitative and quantitative approach (mixed methods) with seventh-grade students as the subjects. The research instruments consisted of Wizer.me digital student worksheets, essay tests, interviews, and observations that had been validated by experts. The data were analyzed to determine the achievement of each indicator of students' critical thinking. The results of this study indicate that the use of Wizer.me media in mathematics learning can help students identify problems with an average score of 53.75 (moderate), analyze relevant information with an average of 70 (high), assess the correctness of calculations with an average of 34.75 (low), and draw logical conclusions with an average of 58.75 (moderate) overall critical thinking skills of 61.63, which is categorized as moderate. In this study, it can be concluded that interactive digital media-based mathematics learning with a real-world context can improve students' critical thinking skills. This is evidenced by the results of research combining digital media such as Wizer.me and the local context of the Grand Mosque of Palembang, which can help make the learning process more meaningful, encourage students to think more analytically, and serve as a reference for teachers to develop innovative and relevant learning strategies for students' lives.